2019
DOI: 10.1111/are.14106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sex‐specific markers and heterogametic XX/XY sex determination system by 2b‐RAD sequencing in redtail catfish (Mystus wyckioides)

Abstract: Sex-specific markers provide significant molecular basis for sex control breeding biotechnology to produce all-male or all-female fish in commercial breeding. Redtail catfish (Mystus wyckioides), one of the commercial bagrid catfishes distributed in Southeast Asian, which have a long sexual maturation period that can last 3-5 years and males have apparent growth advantage over females, but its sex determination system remains unknown. In this study, we first applied 2b-RAD-seq approach to identify three male-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 57 publications
(101 reference statements)
1
9
0
Order By: Relevance
“…After homologous analysis by BLAST, several ORFs were predicted in these female-specific scaffolds, but no potential genes known for sex determination or differentiation within any scaffold. This phenome is similar to most previously reports that even though the sex-specific markers were extended into long segments within hundreds of genes, no sex related genes have been obtained (Pan et al, 2015;Shi et al, 2018;Zhou et al, 2019;Fang et al, 2020). In the future, we will use genome walking to analyze the differences in sequences between male and female individuals.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…After homologous analysis by BLAST, several ORFs were predicted in these female-specific scaffolds, but no potential genes known for sex determination or differentiation within any scaffold. This phenome is similar to most previously reports that even though the sex-specific markers were extended into long segments within hundreds of genes, no sex related genes have been obtained (Pan et al, 2015;Shi et al, 2018;Zhou et al, 2019;Fang et al, 2020). In the future, we will use genome walking to analyze the differences in sequences between male and female individuals.…”
Section: Discussionsupporting
confidence: 87%
“…In many animals, sex determination system has been deduced using sexspecific markers which developed by 2b-RAD-seq. In redtail catfish (Mystus wyckioides), some Y-specific fragments and X-specific fragments have been identified by 2b-RAD-seq, and XX/XY sex determination system was deduced because of the X-specific fragment showing dosage effect between females and males (Zhou et al, 2019). In this study, we revealed that all of the identified sex-specific markers were female-specific, and the identified SNP markers were heterozygous in females but homozygous in males (Figures 1, 2), our data suggest that a ZW/ZZ sex-determination system exists in M. nudus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, it is a famous indigenous fish due to a variety of excellent economic traits such as high protein content, strong disease resistance, easy domestication, and better production performance; it also has ornamental value ( Zhou et al, 2021 ). Therefore, it has recently become an important aquaculture species in China ( Zhou et al, 2019 ; Zhou et al, 2021 ). H. wyckioides exhibits marked sex dimorphism in growth, with the males growing much faster than females.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of next-generation sequencing (NGS) technologies, restriction site-associated DNA sequencing (RADseq) was developed to identify sex-specific markers and discover the mechanisms of sex determination in various species (9)(10)(11). In Mastacembelus armatus, two male-specific DNA fragments and two single nucleotide polymorphisms (SNPs) were identified by RAD-seq, and the Tcl gene was regarded as a candidate sex determination gene (12).…”
Section: Introductionmentioning
confidence: 99%